Protocol-Based Care versus Individualized Management of Patients in the Intensive Care Unit - Siner, Jonathan M.; Connors, Geoffrey R. (Seminars in Respiratory and Critical Care Medicine, 2015)
The delivery of evidence-based care in the high-acuity environment of the intensive care unit can be challenging. In an effort to help turn guidelines and standards of care into consistent and uniform practice, physicians and hospitals turn toward protocol-based medical care. A protocol can help guide a practitioner to make correct interventions, at the right time, and in the proper order when managing a given disease. But to be considered a success, a protocol must meet several standards. A protocol must facilitate consistent practice, guiding the practitioner to deliver care more consistently than without the protocol. A good protocol must also be in alignment with the provider's general practice and beliefs to assure wide adoption and complete penetrance. Finally, the protocol must deliver the most medically correct care—neither simplifying nor overcomplicating health care delivery. In addition to the care the protocol delivers, it must overcome other barriers to gain acceptance. These include concerns about protocol usage among medical trainees, physician concern regarding loss of autonomy, and the ceiling effect protocol-driven care places on expert practitioners, among other concerns. The aim of this article is to critically appraise what it means for a protocol to be considered successful with an aim toward improving protocol design and implementation in the future.
Keywords: intensive care unit; protocol; protocol-based medicine; early goal-directed therapy; spontaneous breathing trials